Correction: Furnier et al. Translating Molecular Technologies into Routine Newborn Screening Practice. Int. J. Neonatal Screen. 2020, 6, 80 - Sarah M. Furnier; Maureen S. Durkin; Mei W. Baker (MDPI AG, 2021)
In the original article [...]